(untitled) (New York, 2005)
This history of the American Republic has a narrative approach, helping students to become involved in the human dramas that shaped history. Essays are included to set American events in a global context, and each chapter ends with a summary to aid learning.
Keywords: United States,Hoa Kỳ; History,Lịch sử